(untitled) (Third Sector Social Economic Review, 2022)
Insurance creates a nationwide fund with the insurance premiums it pays for the product, and while protecting the planet against the possibility of risk and danger, it also expects to complete those that approach it in terms of risks. It has the second share after Turkey’s important insurance business, which will provide confidence in the front and the future. Insurance is a sector in Turkey. The insurance sector is divided into sub-branches as non-life, life, pension and reinsurance. It has a larger share in non-life branches compared to branches. Purpose in this life is analyzed in the top 10 insurance projects in terms of asset size in the branch of life. The event helps him choose a show in a competition setting and shows how to show the best result from available entries. In this study, data envelopment related to the prediction in the top 10 in terms of usage, operating in the insurance sector in Turkey between 2017-2021 was considered. The event was done in a way by dividing the year 4 and separating it. In the use of the analysis made in 2017-2021, the number of companies valid at his time was considered to be 4. The year with all real estate prices was realized as 2017.